The Effect of Implementing the Sepsis Early Goal-Directed Therapy (EGDT) Protocol on Patient Mortality in the Hospital ICU in Cairo, Egypt - Gabbar, Mohammed Abdel; Amr Hassan (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Sepsis is a life-threatening systemic inflammatory syndrome with a high mortality rate. Early goal-directed therapy (EGDT) is a structured therapy protocol that aims to improve tissue perfusion and oxygenation in sepsis patients. Methods: This retrospective observational study analyzed data on sepsis patients in the ICU of a Cairo hospital, Egypt (2020-2023). Patient mortality was compared before and after the implementation of the EGDT protocol. Results: Of the 220 sepsis patients, 120 were treated before and 100 after EGDT implementation. Patient mortality in the EGDT group was significantly lower (12% vs 25%, p<0.05). Conclusion: Implementation of the EGDT protocol can reduce the mortality of sepsis patients in the hospital ICU in Cairo, Egypt.